2020
DOI: 10.1186/s13287-020-01969-0
|View full text |Cite
|
Sign up to set email alerts
|

The combination of trehalose and glycerol: an effective and non-toxic recipe for cryopreservation of human adipose-derived stem cells

Abstract: Background Adipose-derived stem cells (ADSCs) promote tissue regeneration and repair. Cryoprotective agents (CPAs) protect cells from cryodamage during cryopreservation. Safe and efficient cryopreservation of ADSCs is critical for cell-based therapy in clinical applications. However, most CPAs are used at toxic concentrations, limiting their clinical application. Objective The aim of this study is to develop a non-toxic xeno-free novel CPA aiming at achieving high-efficiency and low-risk ADSC cryopreservatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Several studies have reported that using DMSO or DMSO + FBS as CPAs was effective in protecting cell survival and retention volume of the adipose tissue compared with the absence of CPA [ 9 , 22 – 25 ]. However, the use of DMSO and FBS has the risk of toxicity and zoonotic infection [ 18 ]. Furthermore, due to the integrity and complexity of tissue compared with isolated cells, thorough elution of DMSO may be difficult [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that using DMSO or DMSO + FBS as CPAs was effective in protecting cell survival and retention volume of the adipose tissue compared with the absence of CPA [ 9 , 22 – 25 ]. However, the use of DMSO and FBS has the risk of toxicity and zoonotic infection [ 18 ]. Furthermore, due to the integrity and complexity of tissue compared with isolated cells, thorough elution of DMSO may be difficult [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The multi-lineage differentiation capacity of the ASCs was detected as previously described [ 18 ]. Adipogenic differentiation was cultured at a concentration of 10 6 cells/mL in the adipogenic induction medium followed by culture for 14 days.…”
Section: Methodsmentioning
confidence: 99%
“…Physiologically, in unicellular organisms, trehalose is secreted as part of a stress response elicited by environmental discomfort, e.g., through exposure to thermal stress or low humidity, in order to preserve cellular integrity [ 53 ]. Moreover, it has achieved broad applications due to its favorable properties regarding osmoregulation, cryoprotection, and desiccation tolerance [ 54 , 55 ]. According to current biochemical models, trehalose is assumed to either build a protective, cocoon-like matrix around nearby protein structures, to entrap water molecules that are remote from protein structures and reduce protein–water interferences, or stabilize them by the establishment of hydrogen-bonds substituted from water molecules [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…[3,4] Because glycerol molecules can penetrate cell membranes, [5] their presence inside of cells, together with an extensive mixed hydrogen bond (HB) network formation, can result in the dehydration of those cells, slowing down the dynamics of water molecules and preventing the ice-formation during freezing and/or thawing. [6][7][8][9][10] Recently, a contemporary class of green solvents, Deep Eutectic Solvents (DESs), introduced by Abbott et al, [11] are regarded as a potential new type of cryoprotectants. [12,13] DESs are frequently classified as Ionic Liquids' (ILs) analogues.…”
Section: Introductionmentioning
confidence: 99%
“…Because glycerol molecules can penetrate cell membranes, [5] their presence inside of cells, together with an extensive mixed hydrogen bond (HB) network formation, can result in the dehydration of those cells, slowing down the dynamics of water molecules and preventing the ice‐formation during freezing and/or thawing [6–10] …”
Section: Introductionmentioning
confidence: 99%